Butyrate modulates diabetes-linked gut dysbiosis: epigenetic and mechanistic modifications. (January 2020) - Noureldein, Mohamed H; Bitar, Sara; Youssef, Natalie; Azar, Sami; Eid, Assaad A
Abstract : Diabetic dysbiosis has been described as a novel key player in diabetes and diabetic complications. However, the cellular/molecular alterations associated with dysbiosis remain poorly characterized. For that, control, non-obese type 2 diabetic MKR mice and MKR mice treated with butyrate were used to delineate the epigenetic, cellular and molecular mechanisms by which dysbiosis associated with diabetes induces colon shortening and inflammation attesting to gastrointestinal disturbance. Our results show that dysbiosis is associated with T2DM and characterized by reduced Bacteroid fragilis population and butyrate-forming bacteria. The reduction of butyrate-forming bacteria and inadequate butyrate secretion result in alleviating HDAC3 inhibition and altering colon permeability. The observed changes are also associated with an increase in ROS production, a rise in NOX4 proteins, and a shift in the inflammatory markers, where IL-1β is increased and IL-10 and IL-17α are reduced. Treatment with butyrate restores the homeostatic levels of NOX4 and IL-1β. In summary, our data suggest that in T2DM, dysbiosis is associated with a reduction in butyrate content leading to increased HDAC3 activity. Butyrate treatment restores the homeostatic levels of the inflammatory markers and reduces ROS production known to mediate diabetes-induced colon disturbance. Taken together, our results suggest that butyrate could be a potential treatment to attenuate diabetic complications.